The commission of crime from the perspective of decision-making differences - Peng, Jiaxi; Zhang, Jiaxi; Yuan, Weizhuo; Zhou, Xuan; Tian, Jianquan; Fang, Peng (Frontiers in Psychology, 2022)
A criminal act can be regarded as an irrational decision-making process. Therefore, understanding differences in the criminal decision-making process would shed light on criminal behavior. We utilized dual processing theory to propose that offenders’ differences in decision-making may cause them to adopt non-adaptive behaviors, such as high reference point setting, abnormal reward–punishment sensitivity, delayed discounting rate, and decision-making style. Our study compares differences in these indicators between offenders (n = 518) and non-offenders (n = 636) in a diverse sample of Chinese adults. The results showed that compared with non-offenders, offenders had higher relative deprivation, reward sensitivity, and delayed discounting rates but lower punishment sensitivity and vigilance in decision-making. A logistic regression analysis also shows that the above factors were significant predictive indicators for the commission of crimes.